Microbiological Isolates and Antibiotic Susceptibilities: A 10-Year Review of Culture-Proven Endophthalmitis Cases. (4th March 2017) - Liu, Chunhong; Ji, Jian; Li, Shengjie; Wang, Zhujian; Tang, Li; Cao, Wenjun; Sun, Xinghuai
ABSTRACT: Purpose : To review the microbiological spectrum and antibiotic sensitivities of the pathogens that cause culture-proven endophthalmitis and to understand the status and trends of antibiotic susceptibility at a public hospital over a 10-year period. Methods : The data of 577 culture-proven endophthalmitis isolates collected between April 2004 and April 2014 were reviewed retrospectively. The antibiotic sensitivities were determined according to the criteria of the Clinical and Laboratory Standards Institute. The changes in antibiotic susceptibility over the 10 years were subjected to χ 2 tests for trends. Results : Among these isolates, 65% were gram-positive organisms (375), 16.6% were gram-negative organisms (96), and 18.4% were fungi (106). The predominant pathogens were Staphylococcal species ( Staphylococcus epidermidis in 175, other coagulase-negative Staphylococci in 41, and Staphylococcus aureus in 54 cases), followed by Bacillus cereus isolates. The Aspergillus species was the most frequently isolated fungus, and Pseudomonas aeruginosa was the most frequently isolated gram-negative bacteria. The antibiotic susceptibilities of gram-positive bacteria were as follows: vancomycin, 97.6%; levofloxacin, 85.1%; gentamicin, 78.7%; rifampin, 77.2%; ofloxacin, 77.2%; chloramphenicol, 76.4%; and ciprofloxacin, 73.7%. The antibiotic susceptibilities of gram-negative isolates were as follows: ceftazidime, 50.5%; ciprofloxacin, 82.2%; amikacin, 81.3%; tobramycin, 80.2%; imipenem, 79.7%; and gentamicin, 78%. Over the 10-year study, there were significant changes in the antibiotic susceptibilities to the following five antibiotics: vancomycin, imipenem, penicillin G, amikacin, and trimethoprim-sulfamethoxazole (TMP-SMX). Conclusions : Vancomycin remains the most appropriate empirical antibiotic for gram-positive bacteria. The susceptibilities of the gram-negative organisms to ciprofloxacin and amikacin were greater than that to ceftazidime. Trends toward increases in the susceptibilities to the following five antibiotics were observed: vancomycin, imipenem, penicillin G, amikacin, and TMP-SMX.